The Mobile Surgical Outreach Model for women with genital fistula in the Democratic Republic of Congo - Maroti, Raha; Notia, Amisi; Keyser, L; McKinney, J; Berg, M; Mukwege, D (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the PH Mobile Surgical Outreach (MSO) model of care delivery for women with GF and to present data highlighting the program’s scope and clinical impact in 2011-2017. Methods: PH created the MSO program to deliver health services to women with genital fistula (GF) living in remote areas in DRC. The MSO model facilitates reintegration through community education about GF, leveraging local staff in all aspects of care. Outreach trips are organized annually/bi-annually per site, depending on case volume and funding. Site selection is a two-step process: (1) identification of accessible, strategically located hospitals; (2) initial site visit and readiness assessment. This paper presents 2011-2017 MSO activities, including geographic scope, patient and provider outcomes. Results: The MSO team has worked with 43 clinic sites across 12 provinces. Since 2011, they have conducted 77 site visits and provided surgical care for 2,017 women. Table1 summarizes surgeries conducted annually by province, 2011-2017.Table 2 provides a clinical snapshot of 2017 case mix. Conclusions: The MSO model demonstrates feasibility and indicates program successes for capacity-building in skilled medico-surgical care and enhancing community awareness of GF. Training serves to improve local provider skills, strengthens health workforce and offers scalable, sustainable solutions to prevention and treatment.